Re-visiting Design and Development of a Low-Cost Computer on Wheels to support healthcare delivery for Low-Resource Settings - Sinjani, Mtheto; Lungu, Mwabi; Mtonga, Timothy; Deula, Rashid; Douglas, Gerald (Journal of Health Informatics in Africa, 2024)
Background and Purpose: Unlike implementations in high-income country settings which span the entire breadth of a health facility, electronic health record (EHRs) implementations in low- and middle-income countries (LMICs) have mostly been disease specific. Since most disease-specific clinics are ambulatory in nature, the inpatient setting has been largely ignored with regards to EHR implementations in LMICs. Computers on wheels (CoWs) has improved access in high-income country hospital settings, but may not be financially feasible in LMIC settings.  Here we describe the design and development of a low-cost CoW that has been done in a low-income country setting.Methods: We developed a set of functional requirements for a computer on wheels and a design approach for the development of a functional prototype from concept to finished product. We conducted a laboratory function evaluation to assess how the CoW would work.Results: We designed and developed a CoW comprising a cart, computing platform and a docking station for charging.  Our computing platform is based on a Raspberry Pi single board computer with a 7-Inch touchscreen display, thermal label printer and 2-dimensional barcode scanner. The unit is powered by a rechargeable battery providing a runtime of roughly 16 hours between charges.Conclusions: We have demonstrated that fit-for-purpose solutions that may enhance clinical care in an in-patient setting can be designed and developed in an LMIC setting. This approach can reduce barriers to entry for EMR systems in hospitals by making more affordable and locally supportable solutions available.